2014
DOI: 10.1530/joe-14-0075
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-dependent and PDGF-dependent dynamic neurovascular reconstruction in the neurohypophysis of adult mice

Abstract: Hypothalamo-neurohypophysial system (HNS) releases arginine vasopressin (AVP) and oxytocin (OXT) from axonal terminals of the neurohypophysis (NH) into blood circulation for controlling body fluid homeostasis and lactation. Chronic osmotic and suckling stimulations have been shown to cause neurovascular and neuroglial reconstruction in the NH of adult mammals and no study has been reported for vascular dynamics. The aim of this study was to elucidate the occurrence of continuous angiogenesis and growth factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 70 publications
(78 reference statements)
0
42
0
Order By: Relevance
“…Among them, Mest, Srebf1, Adm and Col25a1 were not reported to be expressed by pituicyte before. Vegfa was reported as pituicyte marker in both mice and zebrafish (Anbalagan et al, 2018;Furube et al, 2014). Another prominent pituicyte marker we identified, namely Rax, is a known hypothalamic tanycyte marker which is also expressed in the NH Pak et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Among them, Mest, Srebf1, Adm and Col25a1 were not reported to be expressed by pituicyte before. Vegfa was reported as pituicyte marker in both mice and zebrafish (Anbalagan et al, 2018;Furube et al, 2014). Another prominent pituicyte marker we identified, namely Rax, is a known hypothalamic tanycyte marker which is also expressed in the NH Pak et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…The identified differentially expressed gene clusters revealed by scRNA-Seq correspond to previously characterized cell types. Thus, previous studies reported the appearance of pituicyte (Anbalagan et al, 2018;Furube et al, 2014;Seyama et al, 1980;Wittkowski, 1986;Yamamoto and Nagy, 1993), macrophage/microglia (Kindt et al, 2007;Pow et al, 1989;Sasaki and Nakazato, 1992), and fenestrated endothelia (Stan et al, 1999) in the NH. The identification of IL and epithelial-like cells in the present study is in agreement with other reports of these cells in the mammalian pituitary (Hudson, 2002;Moran et al, 2010) and also matches recent scRNA-Seq analyses of whole mouse pituitary (Cheung et al, 2018;Ho et al, 2018;Mayran et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The experimental procedure was performed according to our previous study (Furube et al, 2014). For the detection of new-born cells, animals received BrdU via intraperitoneal administration (200 mg/kg) or in the drinking water (1 mg/ml).…”
Section: Brdu Immunostainingmentioning
confidence: 99%
“…We recently reported continuous angiogenesis, which accompanies the proliferation and apoptosis in endothelial cells, in the ME , NH and sensory CVOs . Angiogenesis starts at the embryonic period, persists until the early postnatal period, and then becomes quiescent along with the formation of the BBB .…”
mentioning
confidence: 98%